Plant bed treatment with 1,3-dichloropropene for Meloidogyne hapla control in carrots grown in organic soil - Bélair, G.; Fournier, Y. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1997)
The efficacy of plant bed treatment with the fumigant 1,3-dichloropropene (1,3-D) to control Meloidogyne hapla and improve carrot yields was determined in an organic soil under commercial field conditions. The soil was treated with 1,3-D at 56 and 112 L ha-1 either mixed with a rototiller in a 15-cm width band over the row or injected 20 cm deep with a single shank behind the rototiller at a rate of 56 L ha-1. The single injection treatment at the 56 L ha-1 rate provided the best nematode control with the lowest galling indices and the highest yield of marketable carrot roots (66.7 t ha-1 vs. 5 t ha-1 for untreated control). The mixed application method was less effective than the soil injection method, even at twice the rate. In a second field trial, the fumigant was injected at 40 L ha-1 rate through a single shank at 20 cm deep. Soil treatment suppressed galling and significantly increased the number of marketable carrot roots (68.71 ha-1 vs. 11.81 ha-1 control). Plant bed treatment with 1,3-D is an effective alternative to traditional broadcast treatment for control of root-knot nematodes in carrot production on organic soil.